007 The impact of demographic changes on the presentation and outcome of stroke: experiences of the oldest old in the murrumbidgee region. Issue 6 (24th May 2018) - Powell, Alice; Finucane, Paul; Jude, Martin; Mewburn, Jenna; Mohr, Katherine; Kerr, Stephen
Abstract : Introduction: Demographic changes are leading to an ageing population with a disproportionate increase in the oldest old. Stroke is a leading cause of death and disability in Australia and is particularly prevalent in the elderly. The Murrumbidgee region has a population profile that is 14 years ahead of national Australia and therefore data from this population portends how stroke may present nationally in the future. Existing research suggests that stroke risk factors, subtype, treatment provided and outcomes differ between younger and older demographic groups. This study seeks to build a profile of the experiences of stroke in the oldest old and compare variables with two younger cohorts to test a number of hypotheses about background, treatment and outcomes. Methods: Data was collected retrospectively from the electronic medical records of 100 stroke patients consecutively admitted to the Wagga Wagga Rural Referral Hospital Acute Stroke Unit. They were split into three demographic groups; young old, 65–74 old (75 to 84) and oldest old (85 and older) and comparisons were made of baseline functional status and risk factor profile, stroke type, stroke treatment and outcomes. Results: Older people admitted with stroke were more likely to be female with poorer premorbid functional status and higher numbers living in residential care. Atrial fibrillation (p=0.008) and hypertension (p=0.01) were significantly more common with advancing age while rates of smoking (p=0.006) were higher in younger patients. Stroke mechanism was predominantly cardioembolic in older patients and embolic stroke of undetermined source (ESUS) in the youngest group. Stroke severity and stroke treatment did not vary according to age. However, outcomes were poorer with rates of dependency (p=0.03) and residential aged care facility placement (p=0.06) increased among older patients post stroke. Conclusion: These data provide an indication of how stroke may manifest in our ageing population in the future.